2015
DOI: 10.1038/npp.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Centromedial Amygdala Glutamatergic Synapses by the BDNF Val66Met Polymorphism

Abstract: Fear expression is mediated by an activation of the centromedial amygdala (CEm), the major output nucleus of the amygdaloid complex. Consistently, fear extinction is associated with an increased synaptic inhibition as well as a suppression of the excitability of the CEm neurons. However, little is known about the role of CEm glutamatergic synapses in fear regulation and anxiety-like behaviors. The BDNF Val66Met, a single-nucleotide polymorphism in the human BDNF gene, impairs fear extinction and leads to anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…ProBDNF and mature BDNF utilize distinct receptors to mediate divergent neuronal functions suggesting that the two isoforms may also exhibit a differential expression pattern in the developing brain. To address this question, Hempstead and colleagues have generated a knock‐in mouse in which wild‐type (WT) BDNF is expressed with a C‐terminal hemagglutinin (HA) epitope tag ( Bdnf‐HA ) to enhance BDNF protein detection .…”
Section: Expression Patterns For Bdnf Isoforms and Receptors Across Dmentioning
confidence: 99%
“…ProBDNF and mature BDNF utilize distinct receptors to mediate divergent neuronal functions suggesting that the two isoforms may also exhibit a differential expression pattern in the developing brain. To address this question, Hempstead and colleagues have generated a knock‐in mouse in which wild‐type (WT) BDNF is expressed with a C‐terminal hemagglutinin (HA) epitope tag ( Bdnf‐HA ) to enhance BDNF protein detection .…”
Section: Expression Patterns For Bdnf Isoforms and Receptors Across Dmentioning
confidence: 99%
“…Abnormal NMDAR-mediated transmission in AMY, HPC and PFC contributes to altered synaptic plasticity in mice modeling the BDNF Val66Met polymorphism [5557]. Decreased late phase long-term potentiation (LLTP) hippocampal plasticity is also observed in animals where activity-dependent BDNF signaling is selectively attenuated [38].…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies have demonstrated an impairment of synaptic plasticity in the hippocampus, the medial prefrontal cortex and the amygdala by the BDNF Val66Met polymorphism (Bath et al, 2012; Galvin et al, 2015; Ninan et al, 2010; Pattwell et al, 2012). Since corticostriatal plasticity depends upon BDNF-TrkB signaling (Jia et al, 2010), we asked whether the BDNF Val66Met affects synaptic plasticity in the dorsal striatum.…”
Section: Resultsmentioning
confidence: 96%
“…Consistently, the BDNF Val66Met SNP impairs synaptic plasticity in the infralimbic medial prefrontal cortex, the hippocampus and the central amygdala (Bath et al, 2012; Galvin et al, 2015; Ninan et al, 2010; Pattwell et al, 2012). However, it is unknown whether the Val66Met affects synaptic function in the corticostriatal pathway, the impairment of which has been implicated in not only anxiety disorders but also drug abuse (Fumagalli et al, 2007; Furman et al, 2011; Im et al, 2010; Jeanblanc et al, 2009; McGough et al, 2004; Pittenger et al, 2011).…”
Section: Introductionmentioning
confidence: 85%